Inheriting the Eternal: The Philosophy of Perennialism in Education and Its Relevance to Character Development Among Students in Indonesia - Septia Fahiroh; Hanifatun Nisa; Risan Rusli; Romli Romli (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2026)
While studies on the philosophy of education in perennialism have been extensively conducted in Western contexts, its systematic integration with the epistemology of Islamic education in Indonesia has yet to receive adequate attention in the academic literature. This study aims to bridge this gap by analyzing the philosophical relevance of perennialism as developed by Hutchins, Adler, and Bloom in the character development of students in Indonesia during an era of value disruption. Using library research methods and a conceptual-comparative analytical approach to primary and secondary sources, this study yields three main findings. First, there is epistemological alignment between Perennialism and the principles of Islamic education, particularly in the emphasis on transcendent values and the formation of the “insan kamil” (the perfect human being). Second, the integration of perennialism into competency-based curricula in Indonesia is feasible through the reorientation of Islamic values as an epistemological axis. Third, implementation challenges stem from deep-rooted scientific dichotomies, institutional resource constraints, and paradigmatic resistance. The novelty of this research lies in the construction of a synthetic model that brings together perennialist universalism with the particularism of Indonesian Islamic values as a response to the crisis of character in the era of modernization. These findings contribute to the development of a philosophical framework for Islamic education that is both value-grounded and adaptive to contemporary challenges.